Development of Hybrid CNG/Diesel Dual-Fuel Engine in High Load Condition for Marine Debris Vessel - Frengki Mohamad Felayati; Erik Sugianto; Nilam Sari Octaviani (Department of Naval Architecture - Diponegoro University, 2023)
Greenhouse gas (GHG) emissions are the most influential issue in the transportation sector in recent years due to their impact on the environment. Thus, the design of transportation power plants is necessary to ensure the lowest GHG emissions. However, the development of a small vessel power plant is discussed in this study. The small vessel is a marine debris working vessel that has the purpose of collecting marine debris on the water surface with a conveyor. This vessel is designed with a dual-fuel engine fueled by natural gas from CNG and diesel fuel in high load conditions. Furthermore, the power system is designed with a systematical assessment condition based on the operational condition. Moreover, an experiment was conducted to study the performance and emissions of the engine. The hybrid system is designed with several operational conditions, such as sailing, collecting, and maneuvering. Most of the operations can be used in the hybrid dual-fuel system with nearly similar engine torque to diesel mode. The dual-fuel hybrid system has a significantly low engine fuel consumption with low CO2 emissions. However, relatively high NO2 and CO emissions are still considerable.